Prophet qutcast - "Deutscher, Isaac" (Oxford, 1979)
Carlyle once wrote that as Cromwell's biographer he had to drag out the Lord Protector from under a mountain of dead dogs, a huge load of calummy and oblivion. My job, as Trotsky's biographer, has been somewhat similar, with this difference, however, that when I set out to assail my mountain of dead dogs great events were about to strike my mountain of dead dogs great events were about to strike at it with immense force.
Keywords: "Trotsky , Leon Davidovitch -Biography"